2010
DOI: 10.1007/s13233-009-0070-7
|View full text |Cite
|
Sign up to set email alerts
|

Organic-inorganic hard coating layer formation on plastic substrate by UV curing process

Abstract: Efficient methods for making organic-inorganic hard coating layers on a polymethylmethacrylate substrate were developed and optimized to improve the mechanical and optical properties. Colloidal silica was coupled with methacryloxypropyltrimethoxysilane to make Si-O-Si bonds before incorporating them into the organic phase of the monomer and oligomer. A combination of photoinitiators with different absorption bands could utilize the UV light throughout the entire wavelength range to show better curing results t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
4
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 25 publications
(20 reference statements)
0
4
0
Order By: Relevance
“…Various attempts have been made to improve the modulus of bulk plastic materials and surface softness by using organic-inorganic hybrid composites and coating techniques. 13 Recently, polyhedral oligomeric silsesquioxane (POSS) nanocages have attracted attention owing to their observed mechanical and physical enhancement of a variety of organic systems as an inorganic polymer reinforcement (Figure 1c). 14,15 In particular, the incorporation of a reactive group containing POSS facilitates consolidation through simple ultraviolet (UV) or thermal exposure in the presence of suitable additives.…”
Section: Introductionmentioning
confidence: 99%
“…Various attempts have been made to improve the modulus of bulk plastic materials and surface softness by using organic-inorganic hybrid composites and coating techniques. 13 Recently, polyhedral oligomeric silsesquioxane (POSS) nanocages have attracted attention owing to their observed mechanical and physical enhancement of a variety of organic systems as an inorganic polymer reinforcement (Figure 1c). 14,15 In particular, the incorporation of a reactive group containing POSS facilitates consolidation through simple ultraviolet (UV) or thermal exposure in the presence of suitable additives.…”
Section: Introductionmentioning
confidence: 99%
“…Hard coatings of organic-inorganic hybrids emerge and quickly become the target of extensive research since 1990s [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19]. It is found that in most cases the incorporation of inorganic nanoparticles improves the mechanical and thermal properties of plain organic coating considerably.…”
Section: Introductionmentioning
confidence: 99%
“…For example, in previous works, silica nanoparticles containing methacrylate groups have been prepared by reacting with a silane, 3-(trimethoxysilyl)propyl methacrylate (MSMA), in a sol-gel process [8,[19][20][21][22][23][24][25]. The modified silica nanoparticles would undergo co-polymerization with the binder to form a strong organic-inorganic hybrid via a UV-curing process.…”
Section: Introductionmentioning
confidence: 99%
“…Such polymer substrates are usually fabricated by depositing transparent conducting oxide (TCO) film such as tin‐doped In 2 O 3 (ITO) film on a certain transparent polymer film instead of a glass. Common plastic materials as substrates include polyethylene terephthalate (PET), polycarbonate, polypropylene adipate, and polymethyl methacrylate (PMMA), etc. However, these plastic substrates can be severely damaged at high temperature (200°C–300°C for sputtering method) during deposition process, due to their intrinsic low thermal and mechanical properties compared to other inorganic or metal substrates.…”
Section: Introductionmentioning
confidence: 99%